1992
DOI: 10.1302/0301-620x.74b3.1587894
|View full text |Cite
|
Sign up to set email alerts
|

Spinal abnormalities in young fast bowlers

Abstract: The action of fast bowling in the game of cricket is known to cause injuries to the lumbar spine. We studied a group of 16-to 18-year-old fast bowlers, selected for special fraining in Western Australia. All 24 had MR scans of the spine, 22 had radiographs and CI' scans; in 20 the bowling technique was analysed biomechanically.There was a high incidence of back pain and this was always associated with a radiological abnormality.Pars interarticularis defects were diagnosed in 54% and intervertebral disc degener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 0 publications
2
81
0
6
Order By: Relevance
“…The large number of lumbar spine bone stress injuries is not surprising as the incidence of these injuries in cricket fast bowlers has been reported to be between 11-55% [7,8,18] and is considerably higher than the normal population. [19] What this study demonstrates is that those bone stress injuries are clearly related to age.…”
Section: Discussionmentioning
confidence: 99%
“…The large number of lumbar spine bone stress injuries is not surprising as the incidence of these injuries in cricket fast bowlers has been reported to be between 11-55% [7,8,18] and is considerably higher than the normal population. [19] What this study demonstrates is that those bone stress injuries are clearly related to age.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support other international and local studies on cricket-related musculoskeletal pain/injury. 1,[5][6][7][8]11,12 The anatomical sites of the pain were knee (30%), lower back (29%), shoulder (17%), ankle (13%) and thigh (11%) (p<0.0001). The most common anatomical sites were lower extremities (39%), followed by upper extremities (36%) and lower back (18%).…”
Section: Discussionmentioning
confidence: 99%
“…3 International cricket studies mostly concentrate on young fastbowlers and their injuries. 11,12 Dennis et al focused on bowling workloads regarding injury rates in young fast-bowlers. 11 Hardcastle et al focused on spinal abnormalities in young fast-bowlers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A repeated load on the lumbar spine may affect disc degeneration in rowers, because the peak compressive force at the lumbar spine during the drive phase is 4.6 times the body weight 13) . A previous study reported the relationship between disc degeneration in cricket players and counter-rotation 14) . Maximum exertion trunk rotation using a nonlinear thoracolumbar finite element model generated axial compression and shear force on the intervertebral disc 15) .…”
Section: Discussionmentioning
confidence: 99%